2016
DOI: 10.1161/hypertensionaha.115.06981
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Effect of the Nocturnal Blood Pressure Fall in Hypertensive Patients

Abstract: A mbulatory blood pressure (BP) monitoring (ABPM) has been increasingly used in clinical management of hypertension. 1,2 It has been consistently demonstrated that ambulatory 24-hour BPs are better cardiovascular risk predictors than office BPs 2,3 and that average nighttime sleep BPs are generally better predictors of adverse cardiovascular outcomes than average daytime awake BP levels on ABPM.2,4,5 There is a normal circadian BP variability, with higher levels during daytime and a 10% to 20% BP fall during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
179
6
23

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 440 publications
(224 citation statements)
references
References 44 publications
16
179
6
23
Order By: Relevance
“…26 These phenotypes are associated with increased CVD risk, although there are few published data on the prognostic importance of these phenotypes in African Americans. 27 …”
Section: High Blood Pressurementioning
confidence: 99%
“…26 These phenotypes are associated with increased CVD risk, although there are few published data on the prognostic importance of these phenotypes in African Americans. 27 …”
Section: High Blood Pressurementioning
confidence: 99%
“…It has been reported that nondipping and diminished decline in nocturnal BP is associated with organ damage and poor cardiovascular outcomes both in population studies and in hypertensive patients. [46][47][48][49] It is noteworthy that in patients with pharmacological treatment, we did not observe any differences in nocturnal BP declines between groups. So, it is possible that antihypertensive treatment may affect nocturnal BP decline independent of mean BP.…”
mentioning
confidence: 99%
“…Salles et al conducted a large meta-analysis in over three continents to investigate the effect of various dipping patterns on cardiovascular events and stroke [106]. Compared to the normal dipping pattern, individuals with any other dipping pattern at night were found to be at an increased risk of cardiovascular events (OR 1.40, 95% CI 1.20–1.63) and in particular stroke (OR 1.43, 95% CI 1.15–1.77).…”
Section: Ambulatory Blood Pressure Monitoringmentioning
confidence: 99%